2014
DOI: 10.1175/jcli-d-13-00549.1
|View full text |Cite
|
Sign up to set email alerts
|

Summer Arctic Atmospheric Circulation Response to Spring Eurasian Snow Cover and Its Possible Linkage to Accelerated Sea Ice Decrease

Abstract: Anticyclonic circulation has intensified over the Arctic Ocean in summer during recent decades. However, the underlying mechanism is, as yet, not well understood. Here, it is shown that earlier spring Eurasian snowmelt leads to anomalously negative sea level pressure (SLP) over Eurasia and positive SLP over the Arctic, which has strong projection on the negative phase of the northern annular mode (NAM) in summer through the wavemean flow interaction. Specifically, earlier spring snowmelt over Eurasia leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 30 publications
5
39
1
Order By: Relevance
“…In this way, early snow retreat in the WSP encourages a summer circulation pattern with more ridging over the Kolyma Lowland and East Siberian Sea and troughing over the Taymyr Peninsula and Kara Sea. Impacts on circulation persist through summer and are similar to the findings of Matsumura and Yamazaki () and Matsumura et al (), although their work focused on a larger spatial scale. These relationships could be further tested in a future effort using a coupled atmospheric‐ocean‐ice model.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this way, early snow retreat in the WSP encourages a summer circulation pattern with more ridging over the Kolyma Lowland and East Siberian Sea and troughing over the Taymyr Peninsula and Kara Sea. Impacts on circulation persist through summer and are similar to the findings of Matsumura and Yamazaki () and Matsumura et al (), although their work focused on a larger spatial scale. These relationships could be further tested in a future effort using a coupled atmospheric‐ocean‐ice model.…”
Section: Discussionsupporting
confidence: 84%
“…This activity then propagates eastward throughout the summer (Matsumura et al, ; Matsumura & Yamazaki, ). Similarly, Matsumura et al () describe how earlier snowmelt over Eurasia enhances rising motion over the land, and compensating subsidence and adiabatic warming in the Arctic troposphere, favoring a negative phase of the summer Arctic Oscillation (AO). This is manifest as positive sea level pressure (SLP) anomalies over the central Arctic Ocean—a pattern conducive to summer sea ice export through Fram Strait (Ogi & Wallace, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the level of blocking in the Greenland region is an influence both on snow anomalies and the summertime jet or that this feature simply occurred by chance. Matsumura et al (2014) find that early Eurasian snow melt can lead to a negative Arctic Oscillation in summer; although this is an opposite result to that identified here, it supports the possibility of a spring snow cover impact upon summer atmospheric circulation patterns. However, the time and location of snow anomalies is different.…”
Section: Discussioncontrasting
confidence: 60%
“…Barnes 2013;Screen and Simmonds 2013). However, there is also evidence to link earlier Eurasian snowmelt with increased high pressure over the Arctic in summer and a negative annular mode (Matsumura et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The negative trend of the NAO has been strongly associated with the surface and tropospheric warming in northeastern Canada and Greenland since 1979, which could potentially have impacted on the variation of the Arctic sea ice. Matsumura et al (2014) revealed that earlier spring snowmelt over Eurasia causes a warmer land surface and therefore amplified stationary Rossby waves, leading to a deceleration of the subpolar jet. As a result, an anomalous anticyclone emerges over the Arctic Ocean.…”
Section: Arctic Sea Ice: Atmospheric or Oceanic Forcing?mentioning
confidence: 99%